Autonomic Modulation in Patients with Heart Failure Increases Beat-to-Beat Variability of Ventricular Action Potential Duration - Porter, Bradley; Bishop, Martin J.; Claridge, Simon; Behar, Jonathan; Sieniewicz, Benjamin J.; Webb, Jessica; Gould, Justin; O'Neill, Mark; Rinaldi, Christopher A.; Razavi, Reza; Gill, Jaswinder S.; Taggart, Peter (Frontiers in Physiology, 2017)
Background: Exaggerated beat-to-beat variability of ventricular action potential duration (APD) is linked to arrhythmogenesis. Sympathetic stimulation has been shown to increase QT interval variability, but its effect on ventricular APD in humans has not been determined. Methods and Results: 11 heart failure patients with implanted bi-ventricular pacing devices had activation–recovery intervals (ARI, surrogate for APD) recorded from LV epicardial electrodes under constant RV pacing. Sympathetic activity was increased using a standard autonomic challenge (Valsalva) and baroreceptor indices were applied to determine changes in sympathetic stimulation. Two Valsalvas were performed for each study and were repeated, both off and on bisoprolol. In addition sympathetic nerve activity (SNA) was measured from skin electrodes on the thorax using a novel validated method. Autonomic modulation significantly increased mean short-term variability in ARI; off bisoprolol mean STV increased from 3.73±1.3 ms to 5.27±1.04 ms (p=0.01), on bisoprolol mean STV of ARI increased from 4.15±1.14 ms to 4.62±1 ms (p=0.14). Adrenergic indices of the Valsalva demonstrated significantly reduced beta-adrenergic function when on bisoprolol (Δ pressure recovery time, p=0.04; Δ systolic overshoot in Phase IV, p=0.05). Corresponding increases in SNA from rest both off (1.4 uV, p<0.01) and on (0.7 uV, p<0.01) bisoprolol were also seen. Conclusions: Beat-to-beat variability of ventricular APD increases during brief periods of increased sympathetic activity in patients with heart failure. Bisoprolol reduces, but does not eliminate, these effects. This may be important in the genesis of ventricular arrhythmias in heart failure patients.